Histone H3 lysine 9 trimethylation is required for suppressing the expression of an embryonically activated retrotransposon in Xenopus laevis - Herberg, Sarah (Sci Rep, 2015)
Transposable elements in the genome are generally silenced in differentiated somatic cells. However, increasing evidence indicates that some of them are actively transcribed in early embryos and the proper regulation of retrotransposon expression is essential for normal development. Although their developmentally regulated expression has been shown, the mechanisms controlling retrotransposon expression in early embryos are still not well understood. Here, we observe a dynamic expression pattern of retrotransposons with three out of ten examined retrotransposons (1a11, λ-olt 2-1 and xretpos(L)) being transcribed solely during early embryonic development. We also identified a transcript that contains the long terminal repeat (LTR) of λ-olt 2-1 and shows a similar expression pattern to λ-olt 2-1 in early Xenopus embryos. All three retrotransposons are transcribed by RNA polymerase II. Although their expression levels decline during development, the LTRs are marked by histone H3 lysine 4 trimethylation. Furthermore, retrotransposons, especially λ-olt 2-1, are enriched with histone H3 lysine 9 trimethylation (H3K9me3) when their expression is repressed. Overexpression of lysine-specific demethylase 4d removes H3K9me3 marks from Xenopus embryos and inhibits the repression of λ-olt 2-1 after gastrulation. Thus, our study shows that H3K9me3 is important for silencing the developmentally regulated retrotransposon in Xenopus laevis.